Understanding Synergistic Toxicity of Terpenes as Insecticides: Contribution of Metabolic Detoxification in Musca domestica - Scalerandi, Esteban; Flores, Guillermo A.; Palacio, Marcela; Defagó, Maria Teresa; Carpinella, María Cecilia; Valladares, Graciela; Bertoni, Alberto; Palacios, Sara María (Frontiers in Plant Science, 2018)
Essential oils, which are mixtures of terpenes (T), frequently show stronger insecticide activity, i.e. lower lethal dose 50 (LC50), than their most abundant terpenes. Synergy between terpenes provides a plausible explanation, but its demonstration has been elusive. In the present work, we look for an alternative explanation, by considering the influence of insect metabolic detoxification. Basically, we propose a model (metabolic model, MM) in which the LC50 of the major T in a mixture is expected to include a fraction that is detoxified by the insect, whereas a minor T would act unimpeded, showing a lower LC50 than when acting alone. In order to test this idea, we analyzed the effects of inhibiting the P450 detoxification system with piperonyl butoxide (PBO), on the lethal concentration of terpenes as fumigants against Musca domestica. We found that, within a group of 10 terpenes (linalool, citronellal, -pinene, 1,8-cineole, -terpinene, limonene, -terpinene, -pinene, thymol and (R)-pulegone), seven showed LC50PBO (the lethal concentration for PBO-treated flies) between 1.7 and 12.4 times lower than the corresponding LC50 when P450 were not inhibited. Only in one case, that of (R)-pulegone, was LC50PBO greater than LC50, while two terpenes (-pinene and thymol) showed no changes in toxicity. The increased activity of most Ts (particularly linalool and citronellal) in PBO-treated flies supports our idea that normally the LC50 includes a fraction of inactive compound, due to detoxification. Having previously determined that M. domestica preferentially oxidizes the most abundant T in a mixture, while Ts in smaller proportions are poorly or not detoxified by the P450 system, we assessed now whether the toxicity of minority terpenes in a mixture is similar to their activity under P450 inhibition. We chose suitable binary combinations in such a way that one T (in greater proportion) should be the target of P450 while the other (in smaller proportion) should intoxicate the fly with LC50PBO or similar. Combinations of 1,8-cineole citronellal, 1,8-cineole-linalool, linalool-citronellal, (R)-pulegone-linalool, (R)-pulegone-1,8-cineole and (R)-pulegone-citronellal were assayed against M. domestica and the LC50 of each mixture was determined and compared to values predicted by our model (considering the LC50PBO for minor component) or